2014
DOI: 10.1007/s12272-014-0443-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective induction of hepatic cytochrome P450 2B activity by leelamine in vivo, as a potent novel inducer

Abstract: Cytochrome P450 (CYP) is an important enzyme that can act on xenobiotic substances such as toxic chemicals or drugs. Phenobarbital (PB) has been widely used to induce CYP2B activity to investigate the drug-drug interaction of CYP2B substrate drugs. Leelamine is a diterpene compound, and is the current focus of efforts to develop a treatment for diabetes. In this study, we identified the selective and potent inductive effect of leelamine on CYP2B at doses of 5, 10, or 20 mg/kg in male ICR mice for 1 or 3 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…To characterize the CYP activities in the harvested livers, phenacetin O -demethylation (using 80 µM of phenacetin) for CYP1A, dextromethorphan O -demethylation (using 5 µM of dextromethorphan) for CYP2D, and midazolam 1’-hydroxylation (using 5 µM of midazolam) for CYP3A were used as cocktail probe reactions [21,22]. The level of protein in the S9 fraction was determined by Bradford assay [23].…”
Section: Methodsmentioning
confidence: 99%
“…To characterize the CYP activities in the harvested livers, phenacetin O -demethylation (using 80 µM of phenacetin) for CYP1A, dextromethorphan O -demethylation (using 5 µM of dextromethorphan) for CYP2D, and midazolam 1’-hydroxylation (using 5 µM of midazolam) for CYP3A were used as cocktail probe reactions [21,22]. The level of protein in the S9 fraction was determined by Bradford assay [23].…”
Section: Methodsmentioning
confidence: 99%
“…Each assay contained 0.1 M potassium phosphate buffer (pH 7.4), cocktail probe substrates, S9 fraction (20 μL), and a NADPH-generating system (NGS) containing 0.1 M glucose 6-phosphate, 10 mg/mL β-NADPH, and 1.0 U/mL glucose-6-phosphate dehydrogenase, in a final volume of 100 μL. The probe substrate mixture contained 80 μM phenacetin for CYP1A2, 20 μM bupropion for CYP2B, 20 μM omeprazole for CYP2C, 5.0 μM dextromethorphan for CYP2D, and 5 μM midazolam for CYP3A (10). Following a 5 min preincubation period in the absence of probe substrate mixture, the reaction mixture was incubated for 60 min at 37°C, and the reaction was stopped by adding 200 μL acetonitrile (ACN) containing 0.1% formic acid and 5 μM reserpine (as an internal standard, IS).…”
Section: Methodsmentioning
confidence: 99%
“…CYP2B6 is involved in the elimination of drugs such as antidepressants, antivirals, opioids, and anesthetics (9). CYP2B6 is highly inducible by activation and/or translocation of the constitutive androstane receptor (CAR) NR113 or by protein stabilization (10,11). A previous study showed that incubation of the intestinal cancer cell line LS174T with saccharin for 24 hr did not affect the aryl hydrocarbon receptor (AhR) and glucocorticoid receptor (GR) transcriptional activities (12).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, during which chemical modifications of leelamine were made to identify its active site responsible for its anticancer activities, has shown that a suppression of the amino group or its charge may lead to a deletion of its antineoplastic actions, thus indicating that its lysosomotropic as well as its antitumorigenic effect may be mediated by this moiety [28]. Furthermore, a recent discovery made by Sehrawat et al has also suggested a novel potential application of leelamine as a potent antidiabetic agent through the induction of cytochrome P450 2B6 (CYP2B) activity [51].…”
Section: Chemistrymentioning
confidence: 99%
“…Cytochrome P450 (CYP) is a key enzyme, which is considered as the most plentiful phase I drug-metabolizing enzyme in humans and can catalyze xenobiotic compounds such as toxic products or medicines. Recent studies have shown that diabetes is related with a notable reduction in hepatic P450 3A4 enzymatic activity and protein level [51,86]. In leelamine-treated male mice liver, the activity of CYP2B increased almost 4-fold compared to control groups.…”
Section: Other Important Pharmacological Actionsmentioning
confidence: 99%